2005
DOI: 10.1002/ep.10111
|View full text |Cite
|
Sign up to set email alerts
|

Testing of water treatment copolymers for compatibility with polyamide reverse osmosis membranes

Abstract: Cationic polymers used in traditional water , followed by anionic polymers , and finally nonionic polymers . Although PCA of the FTIR spectra did detect differences in polymer-exposed membranes vs. a control, no discernable difference in RO membrane performance was observed. Therefore, under the conditions studied, the issue of "membrane poisoning " caused by organic polymer absorption onto polyamide membranes was minimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Therefore, research on novel coagulants has been particularly active in recent years [10]. Among these studies, the use of inorganic coagulants and organic coagulants together was proved to be effective to treat water and wastewater [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on novel coagulants has been particularly active in recent years [10]. Among these studies, the use of inorganic coagulants and organic coagulants together was proved to be effective to treat water and wastewater [11].…”
Section: Introductionmentioning
confidence: 99%
“…WTSs are composed of materials removed from raw water and the products of chemical coagulation that have been added to the raw water. Their characteristics and compositions are highly variable depending on the characteristics of the water being treated, the type and amount of the coagulant used, and the dewatering method [5,10,12,27,[66][67][68][69]. Therefore, the observed differences in the behaviors of the AS investigated in this study and the ones reported in the literature could be attributed to the variability of the various parameters stated above.…”
Section: Compressibility and Hydraulic Conductivitymentioning
confidence: 96%
“…Their characteristics and compositions are highly variable depending on the characteristics of the water being treated, the type and amount of the coagulant used, and the dewatering method [5,10,12,27,[66][67][68][69]. Their characteristics and compositions are highly variable depending on the characteristics of the water being treated, the type and amount of the coagulant used, and the dewatering method [5,10,12,27,[66][67][68][69].…”
Section: Compressibility and Hydraulic Conductivitymentioning
confidence: 99%
“…Hollow fibers have an extremely high packing density, leading to high permeate production rates, but also generate more fouling than other filtration methods that utilize lower fluxes (Günther et al 2012;Yoon et al 2004). The functional groups introduced into the polymer structure of the membrane control the membrane charge, valence, and strength, while the dissolved species adsorption degree is determined by membrane hydrophobicity, charge, and membrane surface morphology (Gabelich et al 2005;ITRC 2010;Mondal and Wickramasinghe 2008). Separation efficiency depends on solute concentration, applied pressure, water flux rate, and other operational parameters in addition to membrane and feed water properties because of the influence of diffusion (ITRC 2010).…”
Section: Reverse Osmosismentioning
confidence: 99%